Pengaruh bauran promosi terhadap keputusan wisatawan backpacker dalam memilih budget hotel di kabupaten badung - I Gede Artha Suartama; Ida Bagus Ketut Astina; Fanny Maharani Suarka (Jurnal Kepariwisataan dan Hospitalitas, 2020)
Abstract The research motivated by the increasing of accommodation growth in Badung Regency and backpacker trend tourism development that increase with economic accommodation needed. Backpacker is a person or group of people who trave for a relatively long time, with minimal budget, use motorbike as transportation and arrange itinerary independently.The variables used are advertising, personal selling, selling promotion and public relation and publicity. The data obtained through observation, questionnaire, literature study and documentation. Sampling technique using purposive sampling with total of respondent are 170 of backpacker tourists. Data analysis in this research using multiple linear regression to find impact of independent variable to dependent variable by partially and simultaneously. The test gave result simultaneously X’s variable got 15,460 Fcount with Ftabel 2,659. Therefore, partially with result tcount of advertising (X1) 3,080, personal selling (X2) 1,031, sales promotion (X3) 3,149, public relation and publicity (X4) 3,012 with ttabel 1,974 and determination coefficients is 27,3%. Conclusion of the research there are three variable have significantly, advertising (X1), sales promotion (X3), and public relation and publicity (X4) impacts of buying decision of backpacker about budget hotel. Therefore one variable is personal selling (X2) doesn’t give significantly impact. Also there are simultaneously impacts of promotional mix (X) variable to the buying decision of backpacker about budget hotel (Y). While, the dominant variable that impacts buying decision of backpacker about budget hotel in Badung Regency is advertising. Keywords: Backpacker, Budget Hotel, Promotional Mix, Accommodation